THE EVALUATION OF DRUG INTERACTIONS IN PRESCRIPTIONS FOR HEART DISEASE PATIENTS AT THE XYZ PHARMACY IN 2024: DRUG INTERACTIONS - Miftahul Hidayati; Rahmadevi Rahmadevi (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2026)
Background: Cardiovascular disease is a major cause of morbidity and mortality, with treatment commonly involving polypharmacy, which increases the risk of drug interactions. Methods: This study aimed to evaluate potential pharmacokinetic drug interactions in prescriptions of heart disease patients at XYZ Pharmacy in 2024. This study used a descriptive observational design with a retrospective approach through prescription review. A total of 45 prescriptions that met the inclusion criteria were selected using total sampling. Data were analyzed descriptively using frequency and percentage. Results: The results showed that most prescriptions contained 3–4 drugs (62.2%), indicating polypharmacy. A total of 92 potential drug interaction cases were identified, consisting of 79.30% pharmacodynamic interactions and 20.70% pharmacokinetic interactions. Pharmacokinetic interactions occurred during the absorption, distribution, metabolism, and excretion phases, with examples including digoxin–spironolactone, clopidogrel–lansoprazole, and metformin–furosemide. The most common interaction combinations occurred between cardiovascular drugs (54.35%). Conclusion: In conclusion, there are potential pharmacokinetic drug interactions in prescriptions of heart disease patients at XYZ Pharmacy in 2024. These findings highlight the importance of drug interaction screening in pharmaceutical services to improve the safety and effectiveness of therapy.